Brain Tumor-Associated Psychosis and Spirituality—A Case Report - Dutschke, Lars Levi; Steinau, Sarah; Wiest, Roland; Walther, Sebastian (Frontiers in Psychiatry, 2017)
This case report describes a patient with a dysembryogenic neuroepithelial tumor localized in the posterior thalamus and internal capsule, which presented with psychosis including religiously determined severe self-mutilation, auditory hallucinations and rituals. The patient's history includes periodic religiousness over decades of her life suggesting that spirituality in this case might be a symptom of tumor progression. Our case reports on the topology-related effect of lesions on different brain networks involved in the phenomenology of the patient's psychotic symptoms.